Strategi Digital Marketing Dalam Meningkatkan Penjualan Pada UMKM Basreng Sultan Bandung - Devianti, Faysa Firli; Yunita, Tyna (Prisani Cendekia, 2024)
This research was conducted to determine the sales strategy in digital marketing for the SME Basreng Sultan Bandung by identifying marketing strategies and analyzing the SWOT of the product. The use of SWOT aims to understand the strengths, weaknesses, opportunities, and threats of the company. The current rapid economic development impacts company competition, and business actors utilize information technology to develop and promote their products. Basreng Sultan Bandung conducts sales and marketing through social media, which plays an important role in increasing sales and consumer interest. The goal of using digital marketing is to make it easier to market products and for consumers to obtain these products through social media. This research method uses a qualitative approach.